Social capital, knowledge quality, knowledge sharing, and innovation capability: An empirical study of the Indian pharmaceutical sector. (14th November 2019) - Ganguly, Anirban; Talukdar, Asim; Chatterjee, Debdeep
Abstract : Management of technology and innovation is a topic that has been subjected to a lot of discussions by the academicians and practitioners alike. Furthermore, researchers have emphasized the importance of the role that knowledge management/knowledge sharing can play in promoting innovation in an organization. The purpose of this paper is to evaluate the role of social capital and knowledge sharing in achieving innovation capability of an organization. It also discusses the role that knowledge quality might play in fostering the innovation capability of an organization. The basic research model was developed based on an in‐depth review of the extant literature and subsequently tested based on survey data collected from 97 senior executives across multiple pharmaceutical organizations in India. The findings of the partial least squares structural equation modeling indicated that knowledge quality and explicit and tacit knowledge sharing had a significant effect on innovation capability of pharmaceutical organizations in India. It further highlighted that although relational and cognitive social capital play a significant role in improving the quality of shared knowledge among the employees, structural social capital did not have a significant role to play. The findings of this study are expected to aid the pharmaceutical sector to understand the role that knowledge sharing might play in achieving its innovation capability and design knowledge management strategies accordingly.